Voltage Regulation and Power Loss Analysis on 500 kV EHV Transmission Line Krian-Grati - Reza Sarwo Widagdo; I Made Kastiawan; Imam Suri Tauladan; Indra Budi Hermawan (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2025)
The transmission system distributes electricity from power plants to substations before reaching consumers. During this process, obstacles such as power loss and voltage regulation occur, which must meet specific standards to prevent equipment damage. Power loss can result from factors like corona effects and insulator leakage. This study aims to analyze power loss and voltage regulation based on daily peak load data at 14:00 over 15 days, recording current and voltage values on the extra-high voltage Krian-Grati transmission network. This system uses ACSR Gannet conductors with a cross-sectional area of 392.84 mm² and a length of 79.41 km, having a resistance of 0.00086 Ω/km. Manual calculations for short transmission lines show a voltage difference between sending and receiving ends, with the sending voltage being slightly higher due to reactance, preventing a drastic voltage drop. Over 15 days in December 2024, voltage regulation did not exceed the standard maximum of <10%, with the highest recorded value at 4.7%. The highest power loss occurred on day 7 at 0.089 MW, while the lowest was on day 9 at 0.023 MW. The total power loss over 15 days reached 1.024 MW, with a daily average of 0.068 MW.